World Flora Online: Placing taxonomists at the heart of a definitive and comprehensive global resource on the world's plants. Issue 6 (26th November 2020) - Borsch, Thomas; Berendsohn, Walter; Dalcin, Eduardo; Delmas, Maïté; Demissew, Sebsebe; Elliott, Alan; Fritsch, Peter; Fuchs, Anne; Geltman, Dmitry; Güner, Adil; Haevermans, Thomas; Knapp, Sandra; et al.
Abstract: It is time to synthesize the knowledge that has been generated through more than 260 years of botanical exploration, taxonomic and, more recently, phylogenetic research throughout the world. The adoption of an updated Global Strategy for Plant Conservation (GSPC) in 2011 provided the essential impetus for the development of the World Flora Online (WFO) project. The project represents an international, coordinated effort by the botanical community to achieve GSPC Target 1, an electronic Flora of all plants. It will be a first‐ever unique and authoritative global source of information on the world's plant diversity, compiled, curated, moderated and updated by an expert and specialist‐based community (Taxonomic Expert Networks – "TENs" – covering a taxonomic group such as family or order) and actively managed by those who have compiled and contributed the data it includes. Full credit and acknowledgement will be given to the original sources, allowing users to refer back to the primary data. A strength of the project is that it is led and endorsed by a global consortium of more than 40 leading botanical institutions worldwide. A first milestone for producing the World Flora Online is to be accomplished by the end of 2020, but the WFO Consortium is committed to continuing the WFO programme beyond 2020 when it will develop its full impact as the authoritative source of information on the world's plant biodiversity.